A kind of high wear-resistant and low air permeability glass fiber cloth and preparation method thereof

By using polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent and hydroxypropylmethylcellulose compound slurry during the preparation of glass fiber cloth, dust drop caused by yarn friction is solved. The problem of staining is to achieve high wear resistance and low breathability of glass fiber cloth, which improves the dispersion and tensile strength of the yarn bundle, simplifies the production process and reduces costs.

CN118957993BActive Publication Date: 2024-12-27山东兴国大成电子材料有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411446063.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-27
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

During the weaving process, existing glass fiber cloths are dusty due to warp friction, which can easily cause stains when opening fiber, affect quality, and have poor sizing protection effect.

Method used

Using the slurry method, a composite slurry of polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent and hydroxypropylmethylcellulose is slurried through warp yarn, weaving and compensating the fiber opening step. , optimize the slurry preparation sequence and component ratio, improve the slurry compatibility and bond strength, and reduce breathability and dust generation.

Benefits of technology

Achieve high wear-resistant, low breathable fiberglass fabric, improves the dispersion and tensile strength of the yarn bundle, reduces the number of dust and broken silk on the cloth, enhances the adhesive performance, simplifies the production process, and reduces costs and defects. yield rate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A high wear-resistant and low air permeability glass fiber cloth and a preparation method thereof, belonging to the field of glass fiber cloth. The preparation method of the high wear-resistant and low air permeability glass fiber cloth comprises the following steps: warp sizing, warp aligning, weaving and compensatory fiber opening; wherein the slurry raw material used for the sizing comprises polyvinyl alcohol 6-10wt%, 3-aminopropyltrimethoxysilane coupling agent 5-8wt%, hydroxypropylmethylcellulose 2-4wt% and the balance of water by weight percentage. The glass fiber cloth of the present invention has the characteristics of high wear resistance and low air permeability. At the same time, the glass fiber cloth has high tensile strength and good bonding performance, which solves the problem that a large amount of dust will fall due to warp friction during weaving and the glass fiber cloth is easily contaminated when opening.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of glass fiber cloth, and in particular relates to a high-wear-resistant and low-air-permeability glass fiber cloth and a preparation method thereof. Background Art

[0002] Glass fiber cloth is a kind of cloth made of glass fiber yarn, which usually has the characteristics of high temperature resistance, corrosion resistance, electrical insulation, etc. Glass fiber cloth is needed for the base material of glass fiber waterproof tape. The air permeability and tensile strength of the glass fiber cloth are the key indicators of its performance.

[0003] At present, in the preparation process of glass fiber cloth, polyethylene glycol and polyvinyl alcohol are usually used to compound to obtain sizing sizing. During the experiment, it was found that this sizing sizing will drop a lot of dust due to the friction of the warp yarn in the subsequent weaving process, which is easy to cause the glass fiber cloth to be dirty when the fiber is opened. If the fiber is not opened, dust clumps will accumulate on the cloth surface. Both will seriously affect the quality of use of downstream customers. In addition, from the amount of powder loss and the breakage of glass fiber, it can be seen that this type of sizing sizing can play a certain protective role on the treated warp yarn during the production process, but the protective effect is poor, which seriously affects the quality of the glass fiber cloth.

[0004] Patent application CN115522390B discloses a method for preparing glass fiber cloth, including the following steps: warp sizing, weaving, desizing and fiber opening; wherein the sizing raw materials used for the warp sizing include, by weight percentage, 6-8% polyethylene glycol, 1-3% polyvinyl alcohol, 5-6% silane coupling agent, 3-4% acetic acid and the balance of water. This patent reduces the air permeability of the cloth after fiber opening by using a slurry containing silane coupling agent, polyvinyl alcohol and polyethylene glycol before warp weaving, and the pressure required for fiber opening is greatly reduced. However, there is still a problem that a large amount of dust will fall due to the friction of the warp during the weaving process, and the glass fiber cloth is easily contaminated when the fiber is opened. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a highly wear-resistant and low-permeability glass fiber cloth and a preparation method thereof. The glass fiber cloth has the characteristics of high wear resistance and low air permeability. At the same time, the glass fiber cloth has high tensile strength and good bonding properties, which solves the problem that a large amount of dust will fall due to the friction of warp yarns during the weaving process and the glass fiber cloth is easily contaminated when the fiber is opened.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for preparing a highly wear-resistant and low-permeability glass fiber cloth, comprising the following steps: warp sizing, warp doubling, weaving and compensatory fiber opening; wherein the sizing raw materials used for the sizing include, by weight percentage, 6-10wt% of polyvinyl alcohol, 5-8wt% of 3-aminopropyltrimethoxysilane coupling agent, 2-4wt% of hydroxypropyl methylcellulose and the balance of water.

[0007] In the present invention, the slurry raw materials used in the slurrying process include polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent, hydroxypropyl methylcellulose and water.

[0008] In the present invention, in the slurry used for the whole slurry, the weight percentage of the polyvinyl alcohol is 6-10wt%, and it is understandable that the weight percentage can be any specific value of 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value within the range of 6-10wt%. In the present invention, the weight average molecular weight of the polyvinyl alcohol is 170,000-220,000. The polyvinyl alcohol with the molecular weight used in the present invention can be better compatible with 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose and play a role, so that the slurry has good compatibility, excellent sizing performance and bonding strength. If the molecular weight is too small or too large, the sizing performance and bonding strength of the slurry are affected.

[0009] In the present invention, in the slurry used for the whole slurry, the weight percentage of the 3-aminopropyltrimethoxysilane coupling agent is 5-8wt%. It can be understood that the weight percentage can be any specific value of 5wt%, 6wt%, 7wt%, 8wt% or any value within the range of 5-8wt%.

[0010] In the present invention, in the slurry used for the whole pulp, the weight percentage of the hydroxypropyl methylcellulose is 2-4wt%. It can be understood that the weight percentage can be any specific value of 2wt%, 3wt%, 4wt% or any value within the range of 2-4wt%. In the present invention, the methoxy content of the hydroxypropyl methylcellulose is 25-30wt%, and the hydroxypropoxy content is 10-13wt%. In the present invention, the viscosity of the hydroxypropyl methylcellulose is 58000-65000MPa / s. Preferably, the hydroxypropyl methylcellulose is a quick-dissolving hydroxypropyl methylcellulose. The present invention uses hydroxypropyl methylcellulose in the above parameter range. Because it has a suitable viscosity and the number of reactive groups, it can better form a reaction system with polyvinyl alcohol and 3-aminopropyltrimethoxysilane coupling agent, thereby improving the synergistic effect of the three.

[0011] In the present invention, in the slurry used for the whole sizing, the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxy silane coupling agent and hydroxypropyl methyl cellulose is 3-5:2-4:1-2. Preferably, the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxy silane coupling agent and hydroxypropyl methyl cellulose is 4:3:2. The present invention limits the weight ratio of polyvinyl alcohol, 3-aminopropyl trimethoxy silane coupling agent and hydroxypropyl methyl cellulose to the above range, and the synergistic effect of the three is the most obvious, thereby ensuring that the prepared glass fiber cloth has excellent wear resistance and adhesion, while reducing the air permeability of the glass fiber cloth and improving the uniformity of air permeability. If the content of polyvinyl alcohol is too high, the number of dust and broken silk on the cloth surface will increase, the sizing uniformity will deteriorate, and the tensile strength of the glass fiber cloth will decrease; if the content of polyvinyl alcohol is too low, the air permeability of the glass fiber cloth will deteriorate, and the number of broken silk on the cloth surface will increase, the tensile strength will decrease, resulting in poor wear resistance of the glass fiber cloth.

[0012] The inventors found that without adding polyethylene glycol to the sizing agent used for sizing, a synergistic effect can be achieved by adding a certain amount of 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose. The aminopropyl group in the 3-aminopropyltrimethoxysilane coupling agent reacts with the hydroxyl group in the polyvinyl alcohol to form a hydrogen bond, thereby improving the compatibility and bonding strength of the two, and greatly reducing the generation of dust in the yarn bundle during the weaving process; in addition, hydroxypropyl methylcellulose and 3-aminopropyltrimethoxysilane coupling agent can form a dispersion in water, which can effectively improve the uniformity and permeability of the various components of the sizing agent, and improve the uniformity of the warp yarn sizing treatment. Uniformity, reduce the plasticity of polyvinyl alcohol attached to the surface of the yarn bundle, effectively prevent the yarn bundle from bonding, so that the warp yarns are loose and the gaps are smaller, thereby reducing the air permeability; in addition, since the amine group of the 3-aminopropyl trimethoxysilane coupling agent has very high activity, the addition of 3-aminopropyl trimethoxysilane coupling agent significantly increases the lipophilic groups on the surface of the glass fiber, effectively improving the bonding force between polyvinyl alcohol, hydroxypropyl methylcellulose and glass fiber, so that the film formed after the slurry is dried can better adhere to the surface of the glass fiber yarn, with stronger adhesion, which can provide better protection for the glass fiber yarn in weaving and subsequent production. However, its dosage must be strictly controlled. If it is used too much, it will cause the hardness of the glass fiber cloth to be too large, affecting subsequent use.

[0013] In the present invention, the slurry preparation method comprises the following steps:

[0014] (1) Add 2-4 wt% hydroxypropyl methylcellulose into deionized water and stir at room temperature at a stirring speed of 110-130 r / min for 9-11 minutes;

[0015] (2) Add 5-8 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 110-130 r / min for 22-28 min;

[0016] (3) Add 6-10 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 110-130 r / min for 18-22 min to allow the polyvinyl alcohol to fully swell;

[0017] (4) The system obtained in step (3) is heated to 80-90° C. and stirred at a stirring speed of 145-175 r / min for 18-22 min to obtain the slurry.

[0018] In the present invention, in step (1), 2-4wt% of hydroxypropyl methylcellulose is added to deionized water, and stirred at a stirring speed of 110-130r / min for 9-11min at room temperature. In step (1), the stirring speed is 110-130r / min, and it is understood that the stirring speed can be any specific value of 110r / min, 115r / min, 120r / min, 125r / min, 130r / min, or any value within the range of 110-130r / min.

[0019] In the present invention, in step (2), 5-8wt% of 3-aminopropyltrimethoxysilane coupling agent is added, and stirring is continued for 22-28min at a stirring speed of 110-130r / min at room temperature. In the present invention, the full reaction of 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose is achieved through step (2). In step (2), the stirring speed is 110-130r / min. It can be understood that the stirring speed can be any specific value of 110r / min, 115r / min, 120r / min, 125r / min, 130r / min or any value within the range of 110-130r / min.

[0020] In the present invention, in step (3), 6-10 wt% of polyvinyl alcohol is added, and the mixture is stirred at a stirring speed of 110-130 r / min for 18-22 min at room temperature to fully swell the polyvinyl alcohol. In step (3), the stirring speed is 110-130 r / min. It is understood that the stirring speed can be any specific value of 110 r / min, 115 r / min, 120 r / min, 125 r / min, 130 r / min, or any value within the range of 110-130 r / min.

[0021] In the present invention, in step (4), the system obtained in step (3) is heated to 80-90°C and stirred at a stirring speed of 145-175r / min for 18-22min to obtain the slurry. Preferably, the system obtained in step (3) is heated to 80-90°C at a heating speed of 2-3°C / min. In step (4), the stirring speed is 145-175r / min. It can be understood that the stirring speed can be any specific value of 145r / min, 150r / min, 155r / min, 160r / min, 165r / min, 170r / min, 175r / min or any value within the range of 145-175r / min.

[0022] The slurry preparation method and configuration sequence provided by the present invention can ensure that polyvinyl alcohol and 3-aminopropyl trimethoxy silane coupling agent are fully dispersed in water, and that 3-aminopropyl trimethoxy silane coupling agent can fully react with polyvinyl alcohol and hydroxypropyl methylcellulose, thereby ensuring the uniformity of warp sizing, improving the dispersion of glass fiber yarn, improving the tensile strength and abrasion resistance of glass fiber yarn, and effectively improving the bonding performance of glass fiber cloth, thereby eliminating the desizing and coupling agent surface treatment processes. If the configuration sequence is changed, for example, if the coupling agent is added first or last, more fine hydroxypropyl methylcellulose gel particles will be present in the slurry, making the slurry unusable.

[0023] In the present invention, the warp yarn sizing is to pass the warp yarn through a sizing machine and use a sizing agent to sizing the warp yarn into a sizing beam. Preferably, the warp yarn sizing temperature is 85-90°C. It can be understood that the temperature can be any specific value of 85°C, 86°C, 87°C, 88°C, 89°C, 90°C or any value within the range of 85-90°C.

[0024] In the present invention, the warping is to combine the sized warp beams through a warping machine to combine multiple sized warp beams into one weaving beam according to the width and number of warp yarns required.

[0025] In the present invention, the weaving is to form the glass fiber cloth by interweaving the warp and weft yarns through a loom.

[0026] In the present invention, the compensatory fiber opening pressure is 3-5kg. Preferably, the compensatory fiber opening adopts water pressure compensatory fiber opening, and the compensatory fiber opening pressure is 3-5kg, that is, 0.3-0.5MPa pressure, and the water flow is evenly sprayed on the cloth surface through a water needle plate with small circular holes evenly distributed with a diameter of 0.2mm to perform compensatory fiber opening. In the present invention, fiber opening is only used as compensatory fiber opening of the grey cloth, so there is no need for excessively high water pressure and overly complex equipment, which greatly reduces the production cost and effectively improves the production efficiency. At the same time, due to the reduction of processes, the defect generation rate of the product can be better reduced, and the surface quality of the glass fiber cloth is improved.

[0027] According to another aspect of the present invention, there is also provided a high wear-resistant and low air permeability glass fiber cloth prepared according to the above method.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention does not add polyethylene glycol to the sizing material used for sizing, but adds a certain amount of polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent and hydroxypropyl methylcellulose for compounding and synergistic preparation. On the one hand, the aminopropyl group in the 3-aminopropyl trimethoxysilane coupling agent can react with the hydroxyl group in the polyvinyl alcohol to form a hydrogen bond, thereby improving the compatibility and bonding strength of the two, and greatly reducing the generation of dust in the yarn bundle during the weaving process. On the other hand, hydroxypropyl methylcellulose and 3-aminopropyl trimethoxysilane coupling agent can form a dispersion in water, which can effectively improve the uniformity and permeability of each component of the sizing material, improve the uniformity of the warp yarn sizing material, reduce the plasticity of the polyvinyl alcohol attached to the surface of the yarn bundle, and effectively prevent the yarn bundle from bonding, thereby making the warp yarns loose and the gaps smaller, thereby reducing the air permeability.

[0030] (2) The slurry preparation method and configuration sequence provided by the present invention can ensure that polyvinyl alcohol and 3-aminopropyltrimethoxysilane coupling agent are fully dispersed in water, and that 3-aminopropyltrimethoxysilane coupling agent can fully react with polyvinyl alcohol and hydroxypropyl methylcellulose, thereby overcoming the problem that polyvinyl alcohol and hydroxypropyl methylcellulose are easily stratified when mixed and compounded, thereby ensuring the uniformity of warp sizing, improving the dispersion of glass fiber yarn, improving the tensile strength and wear resistance of glass fiber yarn, and effectively improving the bonding performance of glass fiber cloth.

[0031] (3) The preparation method of the high wear-resistant and low air permeability glass fiber cloth provided by the present invention does not require desizing and coupling agent surface treatment processes, and the fiber opening is only used as a compensatory fiber opening of the grey cloth, so there is no need for excessively high water pressure and overly complex equipment, which greatly reduces the production cost and effectively improves the production efficiency. At the same time, due to the reduction of the process, the defect rate of the product can be better reduced, and the surface quality of the glass fiber cloth is improved. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0033] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0034] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0035] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0036] The invention provides a method for preparing a high-wear-resistant and low-air-permeability glass fiber cloth, comprising the following steps: warp sizing, warp doubling, weaving and compensatory fiber opening; wherein the sizing raw materials used for the sizing include 6-10wt% of polyvinyl alcohol, 5-8wt% of 3-aminopropyltrimethoxysilane coupling agent, 2-4wt% of hydroxypropyl methylcellulose and the balance of water in weight percentage.

[0037] In some embodiments, the weight ratio of the polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose is 3-5:2-4:1-2.

[0038] In some embodiments, the hydroxypropyl methylcellulose has a methoxy content of 25-30 wt % and a hydroxypropoxy content of 10-13 wt %.

[0039] In some embodiments, the viscosity of the hydroxypropyl methylcellulose is 58000-65000 MPa / s.

[0040] In some embodiments, the weight average molecular weight of the polyvinyl alcohol is 170,000-220,000.

[0041] In some embodiments, the warp yarn sizing temperature is 85-90°C.

[0042] In some embodiments, the slurry preparation method comprises the following steps:

[0043] (1) Add 2-4 wt% hydroxypropyl methylcellulose into deionized water and stir at room temperature at a stirring speed of 110-130 r / min for 9-11 minutes;

[0044] (2) Add 5-8 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 110-130 r / min for 22-28 min;

[0045] (3) Add 6-10 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 110-130 r / min for 18-22 min to allow the polyvinyl alcohol to fully swell;

[0046] (4) The system obtained in step (3) is heated to 80-90° C. and stirred at a stirring speed of 145-175 r / min for 18-22 min to obtain the slurry.

[0047] In some embodiments, in step (4), the heating rate is 2-3°C / min.

[0048] In some embodiments, the pressure for compensating fiber opening is 3-5 kg.

[0049] The present invention also provides a high-wear-resistant and low-air-permeability glass fiber cloth prepared according to the method.

[0050] The present invention will be described in detail below by way of examples, wherein Example 1 is the best example. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention by way of example, and are not used to limit the present invention.

[0051] The chemical additives used in the examples and comparative examples of the present invention are all commercially available, and their specific information is as follows:

[0052] The warp yarn used was D450 (GB / T18373-2013 weaving yarn code EC5-11*1), purchased from Henan Guangyuan New Materials Co., Ltd.; the weft yarn was G150 (GB / T18373-2013 weaving yarn code EC9-34*1), purchased from Henan Guangyuan New Materials Co., Ltd.; the warp density was 120 yarns / 25mm, and the weft density was 64 yarns / 25mm.

[0053] Polyvinyl alcohol: Mowiol® PVA-224, purchased from Aladdin Reagent Co., Ltd.; 3-aminopropyltrimethoxysilane coupling agent: purchased from Aladdin Reagent Co., Ltd.; Hydroxypropyl methylcellulose A: methoxy content is 30wt%, hydroxypropoxy content is 13wt%, purchased from Shandong Yiteng New Materials Co., Ltd.; Hydroxypropyl methylcellulose B: methoxy content is 25wt%, hydroxypropoxy content is 10wt%, purchased from Shandong Yiteng New Materials Co., Ltd.; phenylaminovinylsilane coupling agent Z6269: purchased from Dow Chemical Co., Ltd.; polyethylene glycol: PEG-4000, purchased from Aladdin Reagent Co., Ltd.

[0054] Example 1

[0055] The preparation method of a high wear-resistant and low air permeability glass fiber cloth described in this embodiment comprises the following steps: warp sizing: the warp yarn is sizing the warp yarn through a sizing machine using a sizing agent to form a sizing shaft, and the sizing temperature is 85°C; warping: the sizing shaft is passed through a warping machine to combine multiple sizing shafts into a weaving shaft according to the width and number of warp yarns required; weaving: the warp and weft yarns are interwoven on a loom to form a glass fiber cloth; compensating fiber opening: water flow is evenly sprayed on the glass fiber cloth surface through a water needle plate with small circular holes evenly distributed with a diameter of 0.2 mm to perform compensating fiber opening, and the compensating fiber opening pressure is 4 kg, and the finished glass fiber cloth is obtained after drying;

[0056] The slurry raw materials used in the whole slurry include 8wt% polyvinyl alcohol, 6wt% 3-aminopropyl trimethoxysilane coupling agent, 4wt% hydroxypropyl methylcellulose A and the balance water in weight percentage; the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent and hydroxypropyl methylcellulose A is 4:3:2; the slurry preparation method includes the following steps:

[0057] (1) Add 4 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0058] (2) Add 6 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min;

[0059] (3) Add 8 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0060] (4) The system obtained in step (3) was heated to 85° C. at a heating rate of 2° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0061] Example 2

[0062] The preparation method of a high wear-resistant and low air permeability glass fiber cloth described in this embodiment comprises the following steps: warp sizing: the warp yarn is sizing the warp yarn through a sizing machine using a sizing agent to form a sizing shaft, and the sizing temperature is 90°C; warping: the sizing shaft is passed through a warping machine to combine multiple sizing shafts into a weaving shaft according to the width and number of warp yarns required; weaving: the warp and weft yarns are interwoven on a loom to form a glass fiber cloth; compensating fiber opening: water flow is evenly sprayed on the glass fiber cloth surface through a water needle plate with small circular holes evenly distributed with a diameter of 0.2 mm to perform compensating fiber opening, and the compensating fiber opening pressure is 3 kg, and the finished glass fiber cloth is obtained after drying;

[0063] The slurry raw materials used in the whole slurry include 6wt% polyvinyl alcohol, 6wt% 3-aminopropyl trimethoxysilane coupling agent, 4wt% hydroxypropyl methylcellulose B and the balance water in weight percentage; the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent and hydroxypropyl methylcellulose B is 3:3:2; the slurry preparation method includes the following steps:

[0064] (1) Add 4 wt% hydroxypropyl methylcellulose B into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0065] (2) Add 6 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min;

[0066] (3) Add 6 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0067] (4) The system obtained in step (3) was heated to 80° C. at a heating rate of 2° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0068] Example 3

[0069] The preparation method of a high wear-resistant and low air permeability glass fiber cloth described in this embodiment comprises the following steps: warp sizing: the warp yarn is sizing the warp yarn through a sizing machine using a sizing agent to form a sizing shaft, and the sizing temperature is 85°C; warping: the sizing shaft is passed through a warping machine to combine multiple sizing shafts into a weaving shaft according to the width and number of warp yarns required; weaving: the warp and weft yarns are interwoven on a loom to form a glass fiber cloth; compensating fiber opening: water flow is evenly sprayed on the glass fiber cloth surface through a water needle plate with small circular holes evenly distributed with a diameter of 0.2 mm to perform compensating fiber opening, and the compensating fiber opening pressure is 4 kg, and the finished glass fiber cloth is obtained after drying;

[0070] The slurry raw materials used in the whole slurry include 10wt% polyvinyl alcohol, 6wt% 3-aminopropyl trimethoxysilane coupling agent, 2wt% hydroxypropyl methylcellulose A and the balance water in weight percentage; the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent and hydroxypropyl methylcellulose A is 5:3:1; the slurry preparation method includes the following steps:

[0071] (1) Add 2 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0072] (2) Add 6 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min;

[0073] (3) Add 10 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0074] (4) The system obtained in step (3) was heated to 85° C. at a heating rate of 3° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0075] Example 4

[0076] The preparation method of a high wear-resistant and low air permeability glass fiber cloth described in this embodiment comprises the following steps: warp sizing: the warp yarn is sizing the warp yarn through a sizing machine using a sizing agent to form a sizing shaft, and the sizing temperature is 85°C; warping: the sizing shaft is passed through a warping machine to combine multiple sizing shafts into a weaving shaft according to the width and number of warp yarns required; weaving: the warp and weft yarns are interwoven on a loom to form a glass fiber cloth; compensating fiber opening: water flow is evenly sprayed on the glass fiber cloth surface through a water needle plate with small circular holes evenly distributed with a diameter of 0.2 mm to perform compensating fiber opening, and the compensating fiber opening pressure is 3 kg, and the finished glass fiber cloth is obtained after drying;

[0077] The slurry raw materials used in the whole slurry include 10wt% polyvinyl alcohol, 5wt% 3-aminopropyl trimethoxysilane coupling agent, 2.5wt% hydroxypropyl methylcellulose A and the balance water in weight percentage; the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent and hydroxypropyl methylcellulose A is 4:2:1; the slurry preparation method includes the following steps:

[0078] (1) Add 2.5 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0079] (2) Add 5 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min;

[0080] (3) Add 10 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0081] (4) The system obtained in step (3) was heated to 80° C. at a heating rate of 3° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0082] Example 5

[0083] The preparation method of a high wear-resistant and low air permeability glass fiber cloth described in this embodiment comprises the following steps: warp sizing: the warp yarn is sizing the warp yarn through a sizing machine using a sizing agent to form a sizing shaft, and the sizing temperature is 85°C; warping: the sizing shaft is passed through a warping machine to combine multiple sizing shafts into a weaving shaft according to the width and number of warp yarns required; weaving: the warp and weft yarns are interwoven on a loom to form a glass fiber cloth; compensating fiber opening: water flow is evenly sprayed on the glass fiber cloth surface through a water needle plate with small circular holes evenly distributed with a diameter of 0.2 mm to perform compensating fiber opening, and the compensating fiber opening pressure is 5 kg, and the finished glass fiber cloth is obtained after drying;

[0084] The slurry raw materials used in the whole slurry include 10wt% polyvinyl alcohol, 8wt% 3-aminopropyl trimethoxysilane coupling agent, 2wt% hydroxypropyl methylcellulose A and the balance water in weight percentage; the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent and hydroxypropyl methylcellulose A is 5:4:1; the slurry preparation method includes the following steps:

[0085] (1) Add 2 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0086] (2) Add 8 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min;

[0087] (3) Add 10 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0088] (4) The system obtained in step (3) was heated to 90° C. at a heating rate of 3° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0089] Comparative Example 1

[0090] The preparation method of the glass fiber cloth of this comparative example is exactly the same as that of Example 1, except that the weight ratio of the polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose is 6:3:1.

[0091] Comparative Example 2

[0092] The preparation method of the glass fiber cloth of this comparative example is exactly the same as that of Example 1, except that the weight ratio of the polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose is 2:3:1.

[0093] Comparative Example 3

[0094] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that hydroxypropyl methylcellulose A is not contained.

[0095] Comparative Example 4

[0096] The preparation method of the glass fiber cloth of this comparative example is exactly the same as that of Example 1, except that the 3-aminopropyltrimethoxysilane coupling agent is replaced by an equal amount of phenylaminovinylsilane coupling agent Z6269.

[0097] Comparative Example 5

[0098] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that the slurry preparation method includes the following steps:

[0099] (1) Add 4 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0100] (2) Add 8 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0101] (3) heating the system obtained in step (2) to 85°C at a heating rate of 2°C / min, and stirring at a stirring rate of 160 r / min for 20 min;

[0102] (4) Add 6 wt % of 3-aminopropyltrimethoxysilane coupling agent, and continue stirring at a stirring speed of 120 r / min at room temperature for 25 min to obtain the slurry.

[0103] Comparative Example 6

[0104] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that the slurry preparation method includes the following steps:

[0105] (1) Add 6 wt% of 3-aminopropyltrimethoxysilane coupling agent into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min.

[0106] (2) Add 4 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0107] (3) Add 8 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 120 r / min for 20 min to allow the polyvinyl alcohol to fully swell;

[0108] (4) The system obtained in step (2) was heated to 85° C. at a heating rate of 2° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0109] Comparative Example 7

[0110] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that the slurry raw materials used in the slurry include 6wt% polyethylene glycol, 2wt% polyvinyl alcohol, 6wt% 3-aminopropyl trimethoxysilane coupling agent, 4wt% hydroxypropyl methylcellulose A and the balance water in weight percentage; the slurry preparation method comprises the following steps:

[0111] (1) Add 4 wt% hydroxypropyl methylcellulose A into deionized water and continue stirring at room temperature at a stirring speed of 120 r / min for 10 min;

[0112] (2) Add 6 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 120 r / min for 25 min;

[0113] (3) Add 2 wt% polyvinyl alcohol and 6 wt% polyethylene glycol, and stir at room temperature at a stirring speed of 120 r / min for 20 min;

[0114] (4) The system obtained in step (3) was heated to 85° C. at a heating rate of 2° C. / min, and stirred at a stirring rate of 160 r / min for 20 min to obtain the slurry.

[0115] Performance Testing

[0116] The performance of 500 m of finished glass fiber cloth prepared in Examples 1-5 and Comparative Examples 1-7 was tested according to the following testing method.

[0117] (1) Sizing rate: After sizing, 100 warp yarns with a length of 1 m were taken from the left, middle and right sides of the warp yarn to form a test unit. The yarns were dried in a closed environment at a temperature of 110 °C for 1 h, and the weight was detected using an electronic balance. The yarns were then simmered in a closed environment at a temperature of 625 °C for 30 min, and the weight was detected using an electronic balance. The weight change before and after simmering was measured, and the sizing rate was calculated. The specific results are shown in Table 1.

[0118] Table 1 Warp yarn sizing rate after sizing of Examples 1-5 and Comparative Examples 1-7

[0119] .

[0120] It can be seen from Table 1 that the sizing rate of the slurries described in Examples 1-5 after sizing is very small, indicating that according to the slurry preparation method and configuration sequence of the present invention, adding a specific amount of polyvinyl alcohol, hydroxypropyl methylcellulose and 3-aminopropyl trimethoxy silane coupling agent effectively improves the uniformity of sizing.

[0121] (2) Performance test of glass fiber cloth before compensatory fiber opening: Before compensatory fiber opening, the air permeability, number of dust on the cloth, number of broken threads on the cloth and tensile strength of the glass fiber cloth were tested. The air permeability and tensile strength in the warp and weft directions were the average values ​​of one inspection unit of 20 m, and the number of dust on the cloth and the number of broken threads on the cloth were the average values ​​of one inspection unit of 100 m. The specific results are shown in Table 2.

[0122] Air permeability: Take a piece of cloth with a width of 30-50cm and a length equal to the width of the cloth, and use an air permeability tester to test it from left to right;

[0123] The number of dust and broken threads on the fabric surface: Use a fabric inspection machine to manually inspect and confirm (observe with the naked eye), with a speed of 10-15m / min.

[0124] Table 2 Performance of glass fiber cloth before compensation fiber opening of Examples 1-5 and Comparative Examples 1-7

[0125] .

[0126] It can be seen from Table 2 that the glass fiber cloth before fiber opening in Examples 1-5 has less dust on the cloth surface and less broken fibers, indicating that the slurry and the specific preparation sequence of the present invention can effectively improve the protective effect of the slurry on the yarn bundle during the manufacturing process, greatly reduce the number of dust and broken fibers on the cloth surface, thereby improving the adhesion and wear resistance of the glass fiber cloth; the glass fiber cloth before fiber opening described in Examples 1-5 has lower air permeability, smaller range, and higher tensile strength, indicating that the slurry preparation method and the specific preparation process of the present invention reduce the air permeability of the glass fiber cloth and improve the uniformity of the air permeability.

[0127] (3) Performance test of glass fiber cloth after compensatory fiber opening: After compensatory fiber opening, the air permeability, number of cloth stains, number of broken fibers on the cloth surface, and tensile strength of the glass fiber cloth were tested. The air permeability and tensile strength in the warp and weft directions were the average values ​​of one inspection unit of 20 m, and the number of cloth stains and broken fibers on the cloth surface were the average values ​​of one inspection unit of 100 m. The specific results are shown in Table 3.

[0128] Air permeability: Take a piece of cloth with a width of 30-50cm and a length equal to the width of the cloth, and use an air permeability tester to test it from left to right;

[0129] The number of fabric stains and broken threads on the fabric: Use a fabric inspection machine to manually inspect and confirm (visual observation), with a speed of 10-15m / min;

[0130] Tensile strength: Take a sample of 2.54cm×15cm in size and use a strength tester to test the tensile strength of the glass fiber cloth in the warp and weft directions (if testing the warp tensile strength, sample according to the length in the warp direction; if testing the weft tensile strength, sample according to the length in the weft direction).

[0131] Table 3 Performance of glass fiber cloth after compensation fiber opening of Examples 1-5 and Comparative Examples 1-7

[0132] .

[0133] It can be seen from Table 3 that in Examples 1-5, there is basically no cloth stain on the cloth surface after fiber opening, the cloth surface has few broken threads and the tensile strength is high, which shows that the slurry and the specific preparation sequence of the present invention can effectively improve the protective effect of the slurry on the yarn bundle during the manufacturing process, greatly reduce the abnormal broken threads on the cloth surface, and significantly and stably improve the wear resistance and tensile strength of the glass fiber cloth; the air permeability of the glass fiber cloth after fiber opening described in Examples 1-5 is low and the range is small, which shows that the slurry and the specific preparation sequence of the present invention reduce the air permeability of the glass fiber cloth and improve the uniformity of the air permeability.

[0134] As shown in Tables 1-3, by comparing Example 1 with Comparative Example 1, the content of polyvinyl alcohol in Comparative Example 1 is high. Although the air permeability of the glass fiber cloth is reduced to a certain extent, the dust and broken wires on the cloth surface are greatly increased, the tensile strength is relatively low, and the warp yarn sizing rate is extremely poor, indicating that the sizing uniformity is poor. By comparing Example 1 with Comparative Example 2, the content of polyvinyl alcohol in Comparative Example 2 is low, the air permeability of the glass fiber cloth is increased, and the extreme difference is increased, indicating that the air permeability of the glass fiber cloth is poor; at the same time, the number of broken wires on the cloth surface is greatly increased, and the tensile strength is reduced, indicating that the protective effect of the slurry on the glass fiber is reduced and the wear resistance is poor. By comparing Example 1 with Comparative Example 3, Comparative Example 3 does not add hydroxypropyl methylcellulose. Although the warp yarn sizing rate is high, the warp yarn sizing rate is extremely poor, the air permeability is extremely poor, and the number of dust and broken wires on the cloth surface is greatly increased. By comparing Example 1 with Comparative Example 4, it can be seen that the 3-aminopropyl trimethoxysilane coupling agent in Comparative Example 4 is replaced with other types of silane coupling agents, and the warp sizing rate is extremely poor and the air permeability is extremely poor, indicating that the sizing uniformity and air permeability uniformity are deteriorated; and the number of broken silk on the cloth surface is greatly increased, and the tensile strength is reduced, indicating that the protective effect of the sizing agent on the glass fiber is reduced and the wear resistance of the glass fiber cloth is reduced. By comparing Example 1 with Comparative Examples 5-6, the warp sizing sizing slurry obtained by changing the preparation order of polyvinyl alcohol, 3-aminopropyl trimethoxysilane coupling agent, and hydroxypropyl methylcellulose cannot be used. By comparing Example 1 with Comparative Example 7, Comparative Example 7 contains a certain amount of polyethylene glycol. Although the air permeability of the glass fiber cloth is reduced to a certain extent, the dust on the cloth surface and the number of broken silk are greatly increased, and the tensile strength is relatively low, indicating that the bonding is deteriorated and the wear resistance is reduced; and the sizing rate and air permeability are extremely poor, indicating that the yarn sizing uniformity and air permeability uniformity are reduced.

[0135] It can be seen that the present invention achieves a synergistic effect between polyvinyl alcohol, 3-aminopropyltrimethoxysilane coupling agent and hydroxypropyl methylcellulose by limiting the slurry composition, the distribution ratio of each component and the preparation method, thereby improving the interfacial bonding performance of the glass fiber cloth and the slurry, so that the glass fiber cloth has the characteristics of high wear resistance and low air permeability. At the same time, the glass fiber cloth has high tensile strength and good bonding performance.

[0136] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a highly wear-resistant and low-permeability glass fiber cloth, characterized in that: The following steps are involved: Warp yarn sizing, warping, weaving and compensatory fiber opening; wherein the sizing material used in the sizing comprises 6-10wt% polyvinyl alcohol, 5-8wt% 3-aminopropyl trimethoxy silane coupling agent, 2-4wt% hydroxypropyl methyl cellulose and the balance water in weight percentage; the weight ratio of the polyvinyl alcohol, 3-aminopropyl trimethoxy silane coupling agent and hydroxypropyl methyl cellulose is 3-5:2-4:1-2; The method for preparing the slurry comprises the following steps: (1) Add 2-4 wt% hydroxypropyl methylcellulose into deionized water and stir at room temperature at a stirring speed of 110-130 r / min for 9-11 minutes; (2) Add 5-8 wt% of 3-aminopropyltrimethoxysilane coupling agent and continue stirring at room temperature at a stirring speed of 110-130 r / min for 22-28 min; (3) Add 6-10 wt% polyvinyl alcohol and stir at room temperature at a stirring speed of 110-130 r / min for 18-22 min to allow the polyvinyl alcohol to fully swell; (4) The system obtained in step (3) is heated to 80-90° C. and stirred at a stirring speed of 145-175 r / min for 18-22 min to obtain the slurry.

2. The method for preparing a highly wear-resistant and low-air-permeable glass fiber cloth according to claim 1, characterized in that: The hydroxypropyl methylcellulose has a methoxy content of 25-30 wt %, and a hydroxypropoxy content of 10-13 wt %.

3. The method for preparing a highly wear-resistant and low-air-permeable glass fiber cloth according to claim 1, characterized in that: The viscosity of the hydroxypropyl methylcellulose is 58000-65000 MPa / s.

4. The method for preparing a highly wear-resistant and low-air-permeable glass fiber cloth according to claim 1, characterized in that: The weight average molecular weight of the polyvinyl alcohol is 170,000-220,000.

5. The method for preparing a highly wear-resistant and low-air-permeability glass fiber cloth according to claim 1, characterized in that: The warp yarn sizing temperature is 85-90°C.

6. The method for preparing a highly wear-resistant and low-air-permeable glass fiber cloth according to claim 1, characterized in that: In step (4), the heating rate is 2-3°C / min.

7. The method for preparing a highly wear-resistant and low-air-permeable glass fiber cloth according to claim 1, characterized in that: The pressure for compensating the fiber opening is 3-5kg.

8. A high wear-resistant and low air permeability glass fiber cloth prepared according to the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A method for preparing glass fiber cloth

    CN115522390B

  • Non-woven glass fabric and production method thereof

    CN114990759A

  • Production method of thin electronic-grade glass fiber cloth

    CN115354494A

  • Preparation method of glass fiber cloth

    CN115522390A

  • Fiber splitting method of glass fiber cloth

    CN115928432A